Perancangan Alat Pemotong Kelapa Muda Tipe Manual - Romansyah, Muhammad Arun; Triono, Bambang (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Unripened coconut is a refreshing drink that is widely consumed by the public. The process of manually cutting unripened coconuts using traditional knives is often time-consuming and labor-intensive, and also carries a high risk of accidents. Therefore, a manual unripened coconut cutting tool was designed to facilitate and accelerate the cutting process of unripened coconuts with a higher level of safety.The manual unripened coconut cutting tool is designed by combining several mechanisms, such as levers, shafts, and knives. This tool works by rotating the unripened coconut on a shaft equipped with a knife. The rotation of the unripened coconut will generate enough friction to cut the unripened coconut skin. This research aims to design and build a safe, easy-to-use, and efficient manual unripened coconuts cutting tool. The research results showed that this tool was able to cut unripened coconuts with an average time of 30 seconds per fruit, which is much faster than using traditional knives which take an average of 1 minute per fruit. This tool is also proven to be safe to use and does not carry a high risk of accidents.